Language service in the sanitary crisis: theories and practices in Chinese context (Sinología hispánica. China Studies Review, 2021)
Language service in the sanitary crisis: theories and practices in Chinese context technological activities, into its definition. In the fight against the COVID-19 crisis, under the frameworkof “emergency linguistics”, Chinese linguists, digital developers and university students carried outlanguage supports in order to solve the communication problems between authorities, health workers,citizens and foreigners living in China. Specifically, they published manuals of Hubei dialects andinstructions in foreign languages and in basic Chinese on how to protect oneself in the pandemic;moreover, they collected information for the needy communities and cared about the internationalstudents’ psychological state. On the other hand, machine and human translation platforms and mobileapplications were created. However, we notice an inconsistency between the theoretical approachesto the term “language service” and the practices in the pandemic, which is why we suggest caution inthe development of new terms and in the integration of theories and practices.